Indonesian Woman Migrant Workers Fighting Inequality and Violence in Burung-Burung Migran - Hiqma Nur Agustina (Journal of Language and Literature, 2021)
The story of Indonesian Migrant Workers or Tenaga Kerja Indonesia (TKI) is a blurred portrait of Indonesian citizens' absence in their own country, presented in Burung-burung Migran by Miranda Harlan. This study aims to expose gender inequality, the dominance of structural oppression systems, and poor treatment of woman migrant workers. They struggle to get out of poverty, unemployed, unskilled, and uneducated. The determination and willingness to change destiny is not in line with the reality that often does not side with them. This study uses a qualitative method, narrative strategies about narrator, and focalizations, and gender concepts. The results showed that the focalization and narrator type in the text are internal focalisator and homodiegetic narrator. The focalisator also shows unequal gender relations, physical and verbal violence, which tends to repress Indonesian woman migrant workers. The writer's narrative strategy is in the form of using words, phrases, and sentences that appropriately reflect the repression of female migrant workers.